Dictation as a Strategy for Scientific Writing: A Review of the Mind-to-paper Approach - Rosenberg, Jacob (British Journal of Healthcare and Medical Research, 2026)
Academic writing for publication poses persistent challenges for researchers across disciplines, especially when high expectations for productivity and clarity place heavy demands on the writing process. Among strategies proposed to support academic writing, dictation—the spoken generation of a manuscript draft—has recently gained attention yet remains underexplored in research on academic writing. This paper reviews existing evidence on dictation as a writing strategy, with a particular focus on its potential benefits for researchers writing scientific papers. Drawing on empirical studies and theoretical perspectives on writing processes, the paper presents the mind-to-paper (MTP) framework as a structured three-phase approach: (1) detailed pre-writing preparation, (2) uninterrupted oral drafting through dictation, and (3) AI-supported transcription followed by revision. Evidence suggests that dictation can facilitate rapid, coherent first drafts, reduce cognitive load during composition, and support fluency by separating idea generation from linguistic refinement. Qualitative findings further indicate that some writers experience flow-like states during dictation, potentially mitigating common barriers such as writing anxiety and perfectionism. The paper discusses the implications of dictation for academic writing pedagogy and development, particularly regarding cognitive processing, fluency, and linguistic simplicity. It concludes that dictation is a promising, underutilized strategy that warrants further investigation across diverse academic writing contexts.